THE RATIONALE OF UNITED STATES BUSINESS GROUPS’ SUPPORT TOWARDS PARIS CLIMATE ACCORD - Thoriq Al Hakim Faizy (Journal of Social and Political Science)
This research aims to find out about the reasons of US business leaders to refuse Trump's decision in withdrawing the US’s commitment from Paris Climate Accord. In this study, the author uses Rational Choice Theory and Green Economy to understand the logical construction that lies behind their refusal and their continuous support for Paris Climate Accord. The author argues that their continued support for Paris Climate Accord is motivated by two factors. First, that US’s participation in Paris Climate Accord will create economic opportunities due to the global wave of energy transition from conventional to renewable energies. Such commitment is also important to reduce business risk related with the loss of potential energy market, as well as the predicted loss from the occurrence of natural calamities related with the global temperature rising. Secondly, that the US’s involvement in Paris Climate Accord is crucial to mitigate global climate change. Through this study, the author contends that Trump's decision to withdraw from Paris Climate Accord is irrational, because it will only weaken the US’s energy-based economy, and endanger environmental sustainability due to climate disasters that can cause harm both to the US’s businesses, as well as to the global societies in general. Keywords: Paris Climate Accord, Energy Transition, Global Market, Decarbonization